Factuality and the Beyond of God: Attempt at an Inversion of Meillassoux’s Speculative Materialism - Lehmann, Sandra (Diakrisis, 2019)
This article stages the confrontation of two approaches to thinking the absolute. On the one hand, it discusses Quentin Meillassoux’s speculative materialism. In suggesting that there is no ultimate ground of being and that only contingency is necessary, Meillassoux takes the notion of the irreducible character of the absolute to its extreme and aporetic consequences. By contrast, I will outline an alternative account of the absolute. Like Meillassoux, I will suggest that the question of the absolute is intrinsically linked to the question of factuality. Yet, in this case, factuality leads to the notion of the beyond of God as the ground of being, inscribing into being the dynamic of a continuous inner transcendence.